Role of hydroxymethyl-glutharyl CoA reductase inhibitors (statins) in rheumatology - J. Kotyla, Przemysław; Śliwińska-Kotyla, Bogna; Lewicki, Maciej; J. Kucharz, Eugeniusz (Reumatologia/Rheumatology, 2005)
Inhibitors of hydroxymethylglutaryl CoA reductase are characterized by very high efficacy in primary or secondary prevention and treatment of cardiovascular disorders. In last years, the evidence was accumulated suggesting that action of statins go far beyond only cholesterol lowering activity. These properties are sometimes called pleiotropic effects and suggested to be independent from lowering cholesterol activity. They include influence upon bone formation, endothelial function, prevention from dementia and effect upon cellular and humoral immunity. Connective tissue disorders are associated with rapid progression of atherosclerotic lesions. Taking into consideration ability of statins to slow down the progression of atherosclerosis as well as their immunosupressive properties, it is suggested to initiate hypolipemic treatment of the patients with this group of compounds. In this paper, we reviewed potential usefulness of statins in rheumatology. The special emphasis was put on targets and mechanism of action of this group of drugs.